Building capacity for evidence-informed decision making: an example from South Africa. (1st June 2018) - Stewart, Ruth; Langer, Laurenz; Wildeman, Russell; Erasmus, Yvonne; Maluwa, Louis Gerald; Jordaan, Sunet; Lötter, Desyreé; Mitchell, Janine; Motha, Precious
Abstract : To maximise the potential impact and acceptability of EIDM capacity building, there is a need for programmes to coordinate their remits within existing systems, playing both 'insider' and 'outsider' roles. Through a review of the South African evidence-policy landscape and analysis of a stakeholder event that brought together EIDM role players, this paper illustrates how one capacity-building programme navigated its position within the national evidence-policy interface. It identifies strategies for improving the acceptability and potential effectiveness of donor-funded EIDM capacity-building activities: understanding the evidence-policy interface, incorporating programmes into the decision-making infrastructure (being an 'insider'), whilst retaining an element of neutrality (being an 'outsider').